Internalization Of Pancasila Value on Local Government Budgeting - Firmansyah, Rizky; Sukoharsono, Eko Ganis; Rosidi; Baridwan, Zaki; Wickramasinghe, Danture (The International Journal of Accounting and Business Society, 2024)
Purpose — The purpose of this study is to unravel the ideological value of the Indonesian nation that is applied strictly to the budgeting system in the public sector, especially local governments. Design/methodology/approach—This research uses a literature study approach. The data is analyzed by describing the facts, which is then followed by an analysis that provides a specific understanding and explanation. Findings—Internalizing Pancasila values in the implementation of a Performance-Based Budget for the public sector can be an option that solves various problems caused by discrepancies between expectations and achievements. Practical implications—Pancasila values function as a stimulus in a performance-based budget system, intending to improve the quality of services to the community. Thus, budgeting in Indonesia is imbued with the philosophical values of Pancasila, namely the values of divinity, humanity, unity, consultative/representation, and justice, which in turn create general welfare for all Indonesian people. Originality/value—The study's results provide a conceptual explanation of the internalization of Pancasila ideological values, which can be considered in solving problems related to the budgeting system in Indonesia. Paper type — Conceptual Research